SURGICAL TREATMENT IN LUMBAR SPONDYLOLISTHESIS: EXPERIENCE WITH 45 PATIENTS - Pasha, Ibrahim Farooq; Qureshi, Muhammed Abid; Haider, Irfan Zafar; Malik, Arsalan Sharif; Qureshi, Muhammad Asad; Tahir, Usama Bin (Journal of Ayub Medical College Abbottabad, 2012)
Background: Spondylolithesis is forward slipping of upper vertebra in relation to its lower one, which at times requires surgery. The objective of present study is to document the outcome of surgical treatment in spondylolisthesis of lumbosacral region. Methods: We reviewed outcome of surgery in 45 patients with spondylolisthesis. Improvement in pain intensity, neurological status and union achieved after surgery was studied. All patients requiring surgical treatment were included in the study. The patients were operated by single spine surgeon. A Performa was made for each patient and records were kept in a custom built Microsoft access database. Results: Majority of our patient were in 4th and 5th decade with some male domination. Pain was main indication for surgery which was excruciating in 6, severe in 33, and moderate in 6 cases. The neurological status was normal in 34 cases while 11 patients had some deficit. L5-S1 was affected in 26, L4-L5 in 13 and multi or high level was found in rest of cases. Slip grade was measured with Meyerding grades, 18 had grade II, 15 had I, 9 had III and 3 had IV spondylolisthesis. Posterior lumbar inter body fusion (PLIF) was done in 24 patients, posterolateral, transforaminal lumbar inter body and anterior inter body fusion in others. Translaminar screw fixation, transpedicular transdiscal transcorporial and Delta fixation in some cases. Pedicle screw fixation was done in most cases, AO fixator internae and 4.5 mm screw in others. Average follow up was 2 years and 5 months, max 5 years and minimum 6 months. Pain relief was achieved in 82%, neurological improvement 60% and union in 91% cases. There was no deterioration of neurological status, two implant failure and one wound infection. Conclusion: Surgical procedure for Spondylolisthesis must be individualised. Young patients with spondylolysis can be treated with osteosynthesis and sparing of motion segment. PLIF provides satisfactory results in majority of low to moderate cases with some reduction. Transpedicular transdiscal transcorprial and delta fixation is good procedure for severe slips in adult. Keywords: Spondylolisthesis, Spondylolysis, Pedicle screw fixation, Posterior lumbar inter body fusion